The Consequence Of Investment Opportunity Set In Strengthening Investment Policy On Profitability In Indonesia: Dampak Ketersediaan Peluang Investasi dalam Memperkuat Kebijakan Investasi terhadap Profitabilitas di Indonesia - Pamungkas, Wihandaru Sotya (Indonesian Journal of Innovation Studies, 2024)
This study investigates the empirical impact of investment policy components—investment cash flow, investment opportunity set (IOS), IOS strengthening investment policy, institutional ownership, and firm size—on the profitability of manufacturing companies that went public before 2015. Analyzing audited financial statements from 2015 to 2020, our results indicate that investment cash flows exhibit no significant influence on profitability. Conversely, the IOS demonstrates a positive effect, further strengthened by its interaction with investment cash flow. Institutional ownership emerges as a positive contributor, along with firm size, both positively impacting profitability. This underscores the crucial role of identifying strategic investment opportunities in enhancing corporate profitability. These findings provide valuable insights for firms seeking to optimize their investment policies and augment financial performance. Highlights: Strategic Investment Opportunities: Emphasizes the pivotal role of identifying and leveraging investment opportunities to enhance corporate profitability. IOS Interaction and Strengthening: Highlights the positive impact of Investment Opportunity Set (IOS) on profitability, further strengthened by its interaction with investment cash flow. Institutional Ownership and Firm Size Influence: Underscores the positive influences of institutional ownership and firm size on corporate profitability, providing actionable insights for optimizing investment policies. Keywords: Investment Policy, Opportunity Set, Cash Flow, Institutional Ownership, Firm Size